2021
DOI: 10.3389/fbioe.2020.621213
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of NADH Dehydrogenase and Alternative Two-Enzyme Systems for Growth of Corynebacterium glutamicum With Glucose, Lactate, and Acetate

Abstract: The oxidation of NADH with the concomitant reduction of a quinone is a crucial step in the metabolism of respiring cells. In this study, we analyzed the relevance of three different NADH oxidation systems in the actinobacterial model organism Corynebacterium glutamicum by characterizing defined mutants lacking the non-proton-pumping NADH dehydrogenase Ndh (Δndh) and/or one of the alternative NADH-oxidizing enzymes, L-lactate dehydrogenase LdhA (ΔldhA) and malate dehydrogenase Mdh (Δmdh). Together with the mena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…RNA-seq analysis from the ST and HL samples revealed that the high-lysine stresses did not affect the expression levels of ndh genes in C. glutamicum . Further physiological experiments showed that deletion of ndh gene did not cause serious effects on cell growth under the tested no-stress condition, which was consistent with previous reports ( Nantapong et al, 2004 ; Maeda et al, 2021 ) ( Figure 6B ). However, under high-lysine stress conditions, the growth curve analysis suggested that the ∆ndh mutant showed clear growth defects as compared with wild-type and complemented strains.…”
Section: Resultssupporting
confidence: 92%
“…RNA-seq analysis from the ST and HL samples revealed that the high-lysine stresses did not affect the expression levels of ndh genes in C. glutamicum . Further physiological experiments showed that deletion of ndh gene did not cause serious effects on cell growth under the tested no-stress condition, which was consistent with previous reports ( Nantapong et al, 2004 ; Maeda et al, 2021 ) ( Figure 6B ). However, under high-lysine stress conditions, the growth curve analysis suggested that the ∆ndh mutant showed clear growth defects as compared with wild-type and complemented strains.…”
Section: Resultssupporting
confidence: 92%
“…54 The selection of an appropriate biocatalyst and strategy can be employed for efficient bioreduction. 55,56 Recombinant E. coli DCF harboring CgCR and FDH was constructed and chosen for whole-cell biocatalysis of 5-HMF using a sodium formate (HCOONa) cosubstrate. HCOONa is nearly neutral in a water system, which might provide a biocompatible environment for E. coli DCF.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…It is widely distributed in nature and participates in catalyzing various types of reactions to prepare a variety of chiral pharmaceutical intermediates, which promote the progress and development of the pharmaceutical industry [ 18 , 19 , 20 ]. At the same time, oxidoreductase also participates in the key steps of biological cell metabolism and energy conversion [ 21 , 22 ], and has considerable research potential in the preparation of sor and environmental treatment fields [ 23 , 24 , 25 ]. However, in the application of oxidoreductase, a coenzyme such as NADH is often needed as a hydride donor to promote the reaction towards catalysis [ 26 ].…”
Section: Introductionmentioning
confidence: 99%